Historyczny rozwój programów działań na rzecz środowiska w Unii Europejskiej - Monika Kosior (Studia Ecologiae et Bioethicae)
The intensive economic development within EU member countries leading to a significant environment pollution invoked in 70’s a strong need to introduce uniform legal regulations of a common pro-ecological policy, therefore, during the Conference in Paris in 1972, the European Commission was obliged to work out particular programs for the environment protection, realization of which was intended to be done in subsequent time intervals. Incorporation of the first two programs led to formulating principle rules of EU ecological policy that up till now are general determinant of environmental protection in Europe. As a result of the following two programs, a complex system of legal and financial protective instruments along with the system for environment screening was worked out. That time, also two important ecological rules were formulated: durability of natural capital, and ensuring the appropriate environment conditions for further generations, these rules are considered as a basis for sustainable development accepted as one of the main targets of EU ecological policy, the continuation of activities for sustainable development can be also found in subsequent programs (including the VI Program planned for realization by 2010) focused on the search for such legal and institutional solutions that would guarantee the equilibrium between the economic development of particular EU members and the improvement of environment status. Here performed analysis of programs for the environment protection allows for presenting not only the following stages of the ecological law formation in European Union but also underlining their role in shaping and realization of the sustainable development concept.